Pentanary chalcopyrite compounds without tetragonal deformation in the heptanary system Cu(Al,Ga,In)(S,Se,Te)(2) - Hock, Rainer; et al. (Solar Energy Materials and Solar Cells, 2007)
The c/a ratios of the nine ternary Cu-III VI2 compounds in the system Cu(Al,Ga,In)(S,Se,Te)(2) range from 1.939 for CuAlSe2 to 2.014 (CuInS2) at room temperature. The validity of. Vegard's law was presumed to determine the tetragonal deformation 1-c/(2a) for all pentanary mixed crystal compounds Cu-(III,III)-(VI-VI)(2). For six of these nine compounds it is possible to achieve zero tetragonal deformation by adjusting the correct cation and anion substitution. The calculations are performed for room temperature as well as for 500 degrees C, which is a typical temperature for the synthesis of thin films of these semiconductor compounds. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: semiconductors; chalcopyrite compounds; alloys